2018
DOI: 10.21475/ajcs.18.12.09.pne1123
|View full text |Cite
|
Sign up to set email alerts
|

Grafting relations in atemoya (Annona x atemoya Mabb.) plants: peroxidase and phenolic compounds

Abstract: The aim of this study was to evaluate if variations in the peroxidase activity (PRX) and the phenolic compounds (PC) concentration in atemoya scion (Annona x atemoya Mabb.) grafted onto different rootstocks are related to incompatibility. The experiment was conducted in a greenhouse, with atemoya scion grafted onto Annona species rootstocks [A. emarginata 'var. terra-fria'; A. emarginata 'var. mirim; A. mucosa and atemoya (homograft)] and these species ungrafted. The evaluations were performed at 30 and 60 day… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 29 publications
0
3
0
Order By: Relevance
“…The higher peroxidase activity detected in the rootstock bark in relation to the scion bark, for several combinations (Table 1), can be attributed to the differences in the degree of lignification of tissues of both parts, considering that this enzyme acts on lignin biosynthesis (PASSARDI et al, 2005;NOCITO et al, 2010;ZARROUK et al, 2010;LIU, 2012;PINA et al, 2012;PEREIRA et al, 2013;FERNÁNDEZ-PÉREZ et al, 2015BARON et al, 2018. Plant lignification is a complex cellular process that occurs in three sequential steps: synthesis of monolignols in the cytosol; transport of monomeric precursors across the plasma membrane; and oxidative polymerization of monolignols to form lignin macromolecules within the cell wall (LIU, 2012).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The higher peroxidase activity detected in the rootstock bark in relation to the scion bark, for several combinations (Table 1), can be attributed to the differences in the degree of lignification of tissues of both parts, considering that this enzyme acts on lignin biosynthesis (PASSARDI et al, 2005;NOCITO et al, 2010;ZARROUK et al, 2010;LIU, 2012;PINA et al, 2012;PEREIRA et al, 2013;FERNÁNDEZ-PÉREZ et al, 2015BARON et al, 2018. Plant lignification is a complex cellular process that occurs in three sequential steps: synthesis of monolignols in the cytosol; transport of monomeric precursors across the plasma membrane; and oxidative polymerization of monolignols to form lignin macromolecules within the cell wall (LIU, 2012).…”
Section: Resultsmentioning
confidence: 99%
“…Herrero et al (2014) reported that, although of great importance, high peroxidase activity cannot be considered as a definitive early diagnosis of incompatibility, since it seems to be more related to cell wall lignification rather than to tissue degradation. Therefore, the role played by peroxidases in lignification does not generally allow justifying the reason for graft incompatibility and should be proposed with caution (BARON et al, 2018).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation